Acceptance Of Accounting Information Systems For Non-Profit Organizations - Permatasari, Carolina Lita; Luhsasi, Dwi Iga (Jurnal Akuntansi, 2024)
This study aims to determine how much users accept accounting information systems when preparing financial reports. Quantitative methods with path analysis techniques are used in this study to facilitate analysis. The population and samples in this study were 30 respondents from users of the accounting information system of the Brayat Pinuji Foundation social organisation with ten social care units spread across the territory of Indonesia. The results obtained from this study are a significant positive effect of perceived convenience on perceived usefulness: perceived convenience on attitude of use, perceived usefulness on attitude of use, perceived convenience on the intensity of usage behaviour, perceived usefulness on the intensity of usage behaviour; usage attitude on the intensity of usage behaviour; and the intensity of usage behaviour on the real use of accounting information systems.